EVALUATION OF TREATMENT OUTCOMES FOR SUPREMATODE HUMERUS FRACTURES IN CHILDREN USING REDUCTION AND PLASTERING AT VIET DUC FRIENDSHIP HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the results of treatment of closed supracondylar humeral fractures in children by traction and plaster cast at Viet Duc Friendship Hospital from May 2025 to July 2025.Subjects and methods: A cross-sectional descriptive study on 56 children with supracondylar humeral fractures treated by traction and plaster cast at Viet Duc Friendship Hospital from May 2025 to July 2025.Results: The most common age group is 6-10 years old, boys are more common than girls with a ratio of 2/1. Common clinical symptoms in order are pain (100%), decreased and loss of function (94.6%), swelling and bruising (91.1%), and limb axis deviation (82.1%). The most common Gartland classification is grade II - III. After 1 month, all children have grade 2 or higher bone calcification. After 3 months, the results were very good (46.4%), good (41.1%), average (7.1%), and poor (5.4%).Conclusion: This method is very effective, easy to perform, and is the first and safe choice in treating supracondylar humeral fractures in children.
Keywords: supracondylar humeral fractures in children, traction and cast.